Research on the nonlinear effects of technological progress on output of manufacturing firms - Ning Wang; Yuanyuan Hong; Ziyu Guo (Journal of Innovation & Knowledge (JIK), 2025)
This study constructs a theoretical framework for technological progress (TP) on firm output (FOP) and examines the nonlinear influence between them. First, the empirical findings indicate that TP has a 'positive U-shaped' correlation with FOP. This impact is particularly pronounced among firms characterized by high technological intensity, older age, location in eastern regions, and presence in high-innovation-policy environments. Second, the TP of enterprises further affects the output of enterprises by affecting their operating expenses, labor costs, and production capacity. Most importantly, this study shows that quality competitiveness plays a significant role in moderating the interaction between TP and FOP. Specifically, in the early stages of TP, the addition of industry quality competitiveness amplifies the inhibitory effect of TP on FOP. However, when TP further develops, quality competitiveness enhances the promotional effect of TP on FOP. In the initial phase of technological advancements, quality competitiveness mitigates the negative influence that TP may exert on FOP. This study contributes to the existing body of knowledge, offering Chinese insights to complement existing research and holding both scholarly and practical relevance for the progression of other emerging economies.
Keywords: L25; O14; O31; 650; Emerging markets; Technological progress; Firm output; Quality competitiveness